Apparent Digestibility of Nutrients in Thirteen Animal‐Based Feedstuffs by the Orange‐spotted Grouper Epinephelus coioides. (29th January 2022) - He, Yuanfa; Wang, Wenjuan; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Chi, Shuyan
Abstract: In this study, the apparent digestibility coefficients (ADCs) of 13 animal‐based feedstuffs were determined for a common aquaculture fish, the Orange‐spotted Grouper Epinephelus coioides . The feedstuffs included five kinds of fish meal (white fish meal [WFM]; low‐temperature‐steam‐dried brown fish meal [LTSBFM]; domestic flame‐dried fish meal; imported flame‐dried fish meal; miscellaneous fish meal [MFM]), two kinds of blood meal (spray‐dried hemoglobin meal; dried‐blood meal [DBM]), and six kinds of animal by‐product meal (chicken meal; meat and bone meal; pork meat meal; fermented feather meal [FFM]; hydrolyzed feather meal [HFM]; shrimp meal). Experimental diets were composed of reference diet at 699 g/kg, yttrium oxide at 1 g/kg (as a tracer), and each tested feedstuff at 300 g/kg. The ADCs of dry matter, crude protein, lipid, gross energy, phosphorus, and amino acids were determined for each experimental diet by the fecal sedimentation method. Overall, the ADCs of dry matter, crude protein, lipid, energy, phosphorus, and amino acids had ranges of 61.39–76.72, 72.23–91.96, 60.75–91.56, 45.20–88.45, 39.61–76.20, and 70.39–96.71%, respectively. The protein ADCs of the WFM (91.96%) and LTSBFM (91.28%) diets were significantly higher than those of the other feeds. The protein ADCs of the remaining tested diets were over 80%, except for those of the MFM, DBM, and HFM diets. The DBM and HFM diets each had the lowest and second‐lowest ADCs of crude protein, lipid, and energy. In conclusion, Orange‐spotted Grouper demonstrated high nutrient digestibility for the tested animal‐based feedstuffs except MFM, DBM, FFM, and HFM. This digestibility information can aid in the formulation of feed substitutes for least cost diets to be used with cultured Orange‐spotted Grouper.